Precedent autonomy should be respected in life-sustaining treatment decisions - Hebron, Allison Leslie (Journal of medical ethics, 2014)
In the 2011 landmark case of W v M, the English Court of Protection ruled that it was unlawful to withdraw artificial nutrition and hydration from a woman who had been in a minimally conscious state for 8 years. From the perspective of the court, the absence of a written advance directive negated the woman’s previous, autonomous interests and, consequently, emphasis was given to her current welfare and well-being. While life itself is a moral good, prolonging life for a person in regular pain with no hope of recovering to a more complete state of awareness simply because that person only verbalized her wishes about her treatment decisions seems to drastically undervalue the principle of autonomy. We refute the notion that it is the role of the court to prolong life insofar as it can and argue that withholding and withdrawing life sustaining technologies from patients in a minimally conscious state can be ethically justified.